DETERMINANTS OF SHARIA FINTECH GROWTH IN INDONESIA: AN INTEGRATIVE ANALYSIS OF MACROECONOMIC INDICATORS AND MONETARY POLICY - Zaki, Muhammad Zaki As Shafi MT (I-Finance Journal, 2025)
The purpose of this study is to determine the influence of macroeconomic factors (inflation and exchange rates) and monetary policy (interest rates and money supply) on the growth of Islamic fintech in Indonesia. The study utilizes data on macroeconomic factors, monetary policy, and the growth of Islamic fintech (specifically Sharia P2P Lending) in Indonesia. The sample consists of 50 monthly observations from May 2021 to June 2025. The analysis technique employed is multiple linear regression, utilizing t-tests and F-tests for hypothesis testing. The results demonstrate that inflation negatively affects the growth of Islamic fintech, whereas the money supply and Bank Indonesia (BI) interest rates have a significant positive impact. In contrast, the exchange rate showed no significant direct influence. Simultaneously, macroeconomic factors and monetary policy significantly affect the growth of Islamic fintech in Indonesia. The study concludes that the primary drivers of Islamic fintech growth are inflation, BI interest rates, and the money supply, while the exchange rate does not play a significant role.